Relationship between happiness and problem solving skills toward resilience among undergraduate students - Yap, Li Min; Long, Xing Hui; Tang, Shoo Chen (2020)
Society nowadays has the issue in mental health especially those undergraduates in term of their life and academic aspects. While past research has shown that happiness and problem-solving skills may affect the resilience level of an individual. This study aims to identify the relationship between happiness and resilience; problem-solving skills and resilience among undergraduate students. The instrument used in this study included the Subjective Happiness Scale (SHS), Problem Solving Inventory (PSI), and Brief Resilience Scale (BRS). There is a total of 280 respondents were recruited from Universiti Tunku Abdul Rahman (UTAR) by the cluster sampling method. Data were collected through a selfadministered questionnaire. This current study identified that happiness is considered one of the elements which positively predict the resilience level of an individual. Other than happiness, problem-solving skills also have a positive relationship toward the resilience level of an individual. Increasing the happiness and problem-solving skills of undergraduate students may affect and increase their resilience level.